Discuter les ordres du roi. Premières expériences du droit de remontrance par les magistrats du parlement de Flandre (1668-1714) - Clotilde Fontaine (Clio@Themis)
In 1701, Louis XIV reminded to the Flemish magistrates that they could not refuse to apply his law. The analyses carried out in the departmental archives reveal the various means used by Flemish magistrates to formulate their claims : dissertation, letters, delegation. Even if they are not used to this right, they employ other means to support their applications gradually.